2018
DOI: 10.12788/ajo.2018.0038
|View full text |Cite
|
Sign up to set email alerts
|

An MRI Analysis of the Pelvis to Determine the Ideal Method for Ultrasound-Guided Bone Marrow Aspiration from the Iliac Crest

Abstract: Use of mesenchymal stem cells from bone marrow has gained significant popularity. The iliac crest has been determined to be an effective site for harvesting mesenchymal stem cells. Review of the literature reveals that multiple techniques are used to harvest bone marrow aspirate from the iliac crest, but the descriptions are based on the experience of various authors as opposed to studied anatomy. A safe, reliable, and reproducible method for aspiration has yet to be studied and described. We hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 11 publications
4
5
0
5
Order By: Relevance
“…The divergence is even wider with measures of contralateral obliquity, measuring at approximately 25° in the new approach, and approximately 50° in the traditional approach. The trajectory angles of needle direction for the new technique are consistent with those described by Hirahara et al [ 18 ]. The presence of sex-related differences in needle trajectory angle in both the traditional and new techniques was expected as studies have often reported sex-related differences in pelvic and iliac crest anatomy [ 25 - 27 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The divergence is even wider with measures of contralateral obliquity, measuring at approximately 25° in the new approach, and approximately 50° in the traditional approach. The trajectory angles of needle direction for the new technique are consistent with those described by Hirahara et al [ 18 ]. The presence of sex-related differences in needle trajectory angle in both the traditional and new techniques was expected as studies have often reported sex-related differences in pelvic and iliac crest anatomy [ 25 - 27 ].…”
Section: Discussionsupporting
confidence: 84%
“…When inserted to a maximum depth of 6 cm, this trajectory may ensure safe passage between the tables of the ilium, while avoiding the greater sciatic notch. A similar BMA approach was described by Hirahara et al [ 18 ], although there were notable differences from our proposed approach. Hirahara et al defined the trajectory as an angle between the vector from the most medial aspect of the PSIS through the ilium and a vector going through the midline of the pelvis, while our study employed a trajectory from the PSIS to the AIIS [ 18 ].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nossos resultados estão de acordo com o que já foi publicado em relação à amplitude de movimento após a RCS, tanto em estudos que utilizaram enxerto autólogo 4 13 23 quanto em estudos que utilizaram enxerto da derme acelular humana. 15 16 17 18…”
Section: Discussionunclassified
“…The probe is then translated contralaterally from the physician, keeping the hyperechoic sacrum visualized. Next, the probe is translated proximally, with the hyperechoic ilium coming into view, while maintaining the hyperechoic sacrum, until the most superficial depth of the ilium is reached, known as the PSIS, contralateral to the examiner [51]. After identification of the PSIS, the most superficial depth is confirmed in both transverse and longitudinal orientation (Figure 4).…”
Section: Ultrasound Imagingmentioning
confidence: 99%